Central Precocious Puberty and Response to GnRHa Therapy in Children with Cerebral Palsy and Moderate to Severe Motor Impairment: Data from a Longitudinal, Case-Control, Multicentre, Italian Study. (16th July 2017) - Bruzzi, Patrizia; Messina, Maria Francesca; Bartoli, Alessandra; Predieri, Barbara; Lucaccioni, Laura; Madeo, Simona Filomena; Verrotti, Alberto; De Luca, Filippo; Iughetti, Lorenzo
Abstract : Background . Children affected by neurodevelopmental disability could experience early pubertal changes at least 20 times more than the general population. Limited data about central precocious puberty (CPP) among children affected by cerebral palsy (CP) are available. Methods . This is a longitudinal, observational, retrospective, case-control study involving 22 children affected by CPP and CP (group A), 22 paired with CP but without CPP (group B), and 22 children with CPP without CP. Auxological, biochemical, and instrumental data were collected at diagnosis of CPP and at 2 follow-up visits. Results . No differences were detected between groups A (at baseline) and B. At diagnosis of CPP, height SDS adjusted for target height (H-TH SDS) was significantly reduced in A than in C (−0.63 ± 1.94 versus 1.56 ± 1.38), while basal LH and oestradiol levels were significantly elevated in A than in C. During follow-up, despite an effective treatment, growth impairment deteriorated in A than in C (Δ H-SDS from diagnosis of CPP to last follow-up: −0.49 ± 0.91 versus 0.21 ± 0.33, p = 0.023 ). Conclusions . Diagnosis of CPP could be partially mislead in CP due to growth failure that got worse during follow-up despite therapy. CPP in CP seems to progress rapidly along time supporting the hypothesis of a more intense activation of hypothalamic-pituitary-gonadal-axis in these patients.